MODERN TREATMENT METHODS IN ONCOGYNECOLOGY - Jamalova Dilnozabonu Zafarovna (Western European Studies, 2025)
Oncogynecology is a rapidly evolving field that integrates innovative diagnostic and therapeutic strategies to improve patient outcomes. This paper explores the latest advancements in the treatment of gynecologic cancers, including targeted therapy, immunotherapy, minimally invasive surgery, and precision medicine. The review also discusses emerging technologies and their impact on survival rates and quality of life
Keywords: oncogynecology; treatment; surgery